2019
DOI: 10.15252/embr.201847451
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic KRAS signaling activates mTORC1 through COUP‐TFII‐mediated lactate production

Abstract: Oncogenic signals contribute to enhanced glycolysis and mTORC1 activity, leading to rapid cell proliferation in cancer. Regulation of glycolysis and mTORC1 by PI3K/Akt signaling is well established, but how KRAS‐induced MEK signaling regulates these pathways remains poorly understood. Here, we report a role for MEK‐driven lactate production in mTORC1 activation in KRAS‐activated cells. KRAS/MEK‐induced upregulation of the chicken ovalbumin upstream promoter transcriptional factor II (COUP‐TFII) increases the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…Riemann et al 33 reported that extracellular acidosis results in a rapid, sustained decrease in intracellular pH (pH i ) and tissue hypoxia, and induces increased transcription factor phosphorylation and tumor cells transcriptional activity 33 . The involvement of lactic acid in cancer has attracted attention only recently, and lactic acid directly contributes to tumor growth and progression (i.e., the lactate anion and protons) as an oxidative fuel and support for angiogenesis and metastasis 34,35 . For example, extracellular lactic acid acidosis causes a lower pH i and higher intracellular lactate concentration, and rescues 4T1 (murine breast cancer) cells from glucose deprivation 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Riemann et al 33 reported that extracellular acidosis results in a rapid, sustained decrease in intracellular pH (pH i ) and tissue hypoxia, and induces increased transcription factor phosphorylation and tumor cells transcriptional activity 33 . The involvement of lactic acid in cancer has attracted attention only recently, and lactic acid directly contributes to tumor growth and progression (i.e., the lactate anion and protons) as an oxidative fuel and support for angiogenesis and metastasis 34,35 . For example, extracellular lactic acid acidosis causes a lower pH i and higher intracellular lactate concentration, and rescues 4T1 (murine breast cancer) cells from glucose deprivation 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have already shown that the siRNA knockdown of ERα in MCF-7 breast cancer cells decreased COUP-TFII expression while treatment with estradiol increased the expression of COUP-TFII, revealing a positive correlation between COUP-TFII and ERα status (104). A recent study also reported another mechanism of how COUF-TFII might influence LAM pathogenesis, in which lactate production induced by upregulated COUP-TFII in KRAS-activated cells increases mTORC1 activity by disrupting the interaction of TSC2 and Rheb (105) (Figure 1). Thus, NR2F2 could be a promising candidate to explain the gene origin of S-LAM and pathogenesis of LAM.…”
Section: Nr2f2 Located By Gwas In S-lam Patientsmentioning
confidence: 91%
“…Besides serving as a nutrient, lactate may play a role in SSC maturation. Similarly to cancer cells, in which lactate was shown to enhance mTOR activity [ 215 ], it also contributes to the activation of AKT [ 216 ], inhibits apoptosis [ 217 ], and enhances transcription and translation through-put [ 218 ] in male germ cells.…”
Section: Metabolic Regulation Within the Testismentioning
confidence: 99%